“Eighth Wonder of the World:” The Cariboo Wagon Road as British Columbia’s First Megaproject - LEONARD, FRANK (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2016)
Interpretations of the creation and operation of the Cariboo Wagon Road, constructed during the 1860s to the gold fields in the northern interior of colonial British Columbia, range from a marvelous, essential conduit to a costly, superfluous thoroughfare. In our age of cost overruns, it is appropriate to begin a process of addressing cost-effectiveness in evaluating the colony’s largest infrastructure project. After clarifying the structure’s name and extent, this paper collates the relevant British Columbia colonial accounts to establish a global government first cost of the project and compares this expenditure with the cost of goldfield roads in California and Victoria colony, Australia. It then engages with the theory and practice of megaproject analysis in two ways. First, if offers a brief comparison of select primary sources concerning the Cariboo Wagon Road with some of the very different documents that support studies of major projects in the post-war period. It then deploys elements from the growing planning literature concerning megaprojects that allow analysis within the very constraints of the colonial sources. Such an endeavour illuminates some of the shortcomings and gaps in nineteenth-century calculations and understandings of the financial viability of the project.